2017
DOI: 10.1088/1361-6579/aa5c7b
|View full text |Cite
|
Sign up to set email alerts
|

Bioimpedance measurements in dentistry to detect inflammation: numerical modelling and experimental results

Abstract: Such a measure could be integrated in electromedical devices designed, for example, for the therapy of peri-implantitis, in order to personalise the therapeutic dose in terms of intensity and duration and focusing it on the impaired area, minimising the effects on the surrounding tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…This work showed only small changes in the impedance characteristics of the implant when measured over 1 h of implantation. Other work utilized two-electrode EIS to evaluate inflammation surrounding dental implants in vivo [132]. In this study, the impedance was assessed between the titanium implant and a smaller steel electrode attached to different points on the gingiva in an attempt to localize the site of inflammation.…”
Section: Electrochemical Impedance For Assessing Osseointegration (Summary Provided In Table 5)mentioning
confidence: 99%
See 1 more Smart Citation
“…This work showed only small changes in the impedance characteristics of the implant when measured over 1 h of implantation. Other work utilized two-electrode EIS to evaluate inflammation surrounding dental implants in vivo [132]. In this study, the impedance was assessed between the titanium implant and a smaller steel electrode attached to different points on the gingiva in an attempt to localize the site of inflammation.…”
Section: Electrochemical Impedance For Assessing Osseointegration (Summary Provided In Table 5)mentioning
confidence: 99%
“…It was found that the implants with inflammation had a 35% decrease in impedance modulus, which was attributed to hyperaemia in the surrounding tissue. Periimplantitis decreased the impedance modulus by 56%, which was attributed to loss of bone surrounding the implant [132]. EIS has also been applied to assess cochlear implants.…”
Section: Electrochemical Impedance For Assessing Osseointegration (Summary Provided In Table 5)mentioning
confidence: 99%
“…In biomedical applications, NIRS gathers information about tissue compositions, and characterizes materials. [6][7][8]…”
Section: Near-infrared Spectroscopymentioning
confidence: 99%
“…As the diagnosis of inflammation of periodontal and peri-implantal tissues in dentistry is done by naked-eye observation of hyperemia or edema, the bioimpedance measurements were suggested to be effectively used in another study to detect these areas both before and after treatment (18).…”
Section: Inflammationmentioning
confidence: 99%